(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2013)
The most true and sensible quote ’Health is Wealth’ is deliberated whenever there is a point of discussion on healthcare. Healthcare is primary concern for every human being and also for the stakeholders of health care industry. Healthcare services now days are gauged with Quality, Cost and Delivery parameters for evaluation. This paper aims at providing the analytical view on the healthcare services provided through Retail Medical Clinics in Delhi. The landscape of retail medical clinics and their contribution for affordable and accessible healthcare to the people across the social and economic class has been critically analyzed in the paper. This paper highlights the innovative way of providing healthcare with strategies adopted by the pharmacies, retail clinic owners for a profitable business. It has been expected that this new sector of retail medical clinics will emerge as a leading healthcare provider, while growing its scope of services with respect to location and better health plans for the customers. The issue of healthcare services such as inaccessible primary health care services, unnecessary healthcare expenditure borne by the customer and emergency requirement of healthcare fulfillment are addressed in the paper and how the Retail Medical Clinics will be beneficial is deliberated in the paper. The growth and evolution of retail medical clinics highlight opportunities with innovative ways other than the traditional way of delivery of health care services through doctors at hospitals and with an improved value proposition for the Indian health care system.